A text classification method based on a convolutional and bidirectional long short-term memory model. Issue 1 (31st December 2022) - Huan, Hai; Guo, Zelin; Cai, Tingting; He, Zichen
Abstract : Text classification refers to labelling text with specified labels, and it is widely used in public opinion supervision, spam detection, and other fields. However, due to the complex semantics of natural language and the difficulty of extracting semantic features, users of traditional methods encounter difficulties when trying to achieve better classification results. In response to this problem, a text classification method based on the CBM (Convolutional and Bi-LSTM Model) model, which can extract shallow local semantic features and deep global semantic features, is proposed. First, the text is vectorised using the Glove model in the embedding layer. Then, the vector text is sent to the Multiscale Convolutional Neural Network (MCNN) and the Bidirectional Long Short-Term Memory network (Bi-LSTM) respectively. The Bi-LSTM layer is also designed in the present work with use of mixed attention to extract deeper semantic features. Finally, the MCNN features and Bi-LSTM features are fused and sent to the softmax layer for classification. Experimental results show that the model can significantly improve the accuracy of text classification.